The explanation of educational disparities in adiposity by lifestyle, socioeconomic and mental health mediators: a multiple mediation model - Bartoskova Polcrova, Anna; Ksinan, Albert J; González-Rivas, Juan P; Bobak, Martin; Pikhart, Hynek (European journal of clinical nutrition, 2024)
BACKGROUND: The inverse association between education and obesity was previously found in numerous studies. This study aims to assess several possible mediators in the educational disparities in adiposity. We hypothesize the potential mediating role of lifestyle, socioeconomic, and mental health factors in the association between education and adiposity. METHODS: Cross-sectional population-based sample from Czechia included 2,154 25-64 years old subjects (54.6% women). Education was classified as high, middle, and low. Adiposity was assessed as a latent variable based on body fat percentage, BMI, waist circumference, and visceral fat. The mediation potential of unhealthy dietary behavior, alcohol intake, smoking, sedentary behaviors, income, stress, depression, and quality of life was assessed in age-adjusted sex-specific multiple mediation models. RESULTS: The negative direct effect of education on adiposity was statistically significant at 5% level of significance in both sexes. For men, the indirect effect was statistically significant via sedentary behavior (β = 0.041; 95% CI [0.025-0.062]) with a mediation ratio of 23.7%. In women, the indirect effect was statistically significant via dietary risk (β = -0.023, 95% CI [-0.037, -0.013]), alcohol intake (β = -0.006; 95% CI [-0.014, -0.001]), sedentary behavior (β = 0.012, 95% CI [0.004,0.023]), income (β = -0.022; 95% CI [-0.041, -0.004]), and mental health (β = -0.007; 95% CI [-0.019, -0.001]). The total mediation ratio in women was 30.5%. CONCLUSIONS: Sedentary behaviors had mediating role in the association between education and adiposity in both sexes, with more important role in men. In addition, unhealthy diet and lower income partially mediated the educational gradient in adiposity in women.
Keywords: Male; socioekonomické faktory; lidé středního věku; Life Style; Socioeconomic Factors; sedavý životní styl; adipozita; Sedentary Behavior; Humans; obezita; Middle Aged; Obesity; stupeň vzdělání; Czech Republic; Česká republika; mužské pohlaví; Female; Educational Status; průřezové studie; Mediation Analysis; duševní zdraví; Cross-Sectional Studies; ženské pohlaví; Adiposity; Mental Health; disparity zdravotního stavu; Adult; Health Status Disparities; lidé; dospělí; životní styl; analýza mediace